2010
DOI: 10.4236/ijcns.2010.34050
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Modelling for Future Wireless Sensor Network on Surface of the Moon

Abstract: In order to study lunar regolith properties, wireless sensor network is planned to be deployed on surface of the Moon. This network can be deployed having few wireless sensor nodes capable of measuring soil properties and communicating results, as and when ready. Communication scenario on lunar surface is quite different as compared to that on the Earth, as there is no atmosphere and also there are lots of craters as well as various terrain topologies. Since the deployment of sensors on the Moon is a challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Their results indicate that path loss in the lunar surface environment is much more severe than free-space propagation and is affected by the operating frequency and lunar surface soil. In addition, the study by Pabari et al showed that deploying a relaying sensor is an alternative way of ensuring lunar communication under the area coverage with a constrained signal strength [ 14 ]. Some meaningful works focusing on the interaction between EM waves and the dusty plasma have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate that path loss in the lunar surface environment is much more severe than free-space propagation and is affected by the operating frequency and lunar surface soil. In addition, the study by Pabari et al showed that deploying a relaying sensor is an alternative way of ensuring lunar communication under the area coverage with a constrained signal strength [ 14 ]. Some meaningful works focusing on the interaction between EM waves and the dusty plasma have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The study covers different deployment topologies with their costs, coverage and connectivity properties. The following study by Pabari et al (2010) searched the radio signal coverage patterns of four lunar terrains by examining real digital elevation model data of the Moon. Prasad and Murty (2011) and Pabari et al (2013) proposed to use WSNs for in situ exploration of lunar water or ice.…”
Section: Introductionmentioning
confidence: 99%
“…Chukkala et al provided simulation of the Mars Radio Frequency (RF) environment [1]. Pabari et al explain the new radio propagation model for the moon [6]. The operating frequency is 2.4 GHz in the present application scenario, and deployment of sensor on the surface of Mars, where functioning conditions differ from those on Earth.…”
Section: Introductionmentioning
confidence: 99%